RECOVERY OF COPPER FROM PRINTED CIRCUIT BOARDS OF COMPUTERS - Abbas Habeeb Hasson, Hijran Z. Toama (International Journal of Research Science and Management, 2019)
Electronic waste contains many types of metals that can be recovered. In this study the recovery of gold as a precious metal and copper as a base metal from printed circuit boards (PCBs) of consumed computers was investigated.The results of chemical analysis of (PCBs) sample, after preparation by manual separation, cutting, grinding, and sieving, showed that it contain; copper (36.268%). Hydrometallurgical method by leaching and precipitation process was applied for copper recovery. The parameters for leaching by nitric acid were; temperatures (50, 60, 70 and 80 oC), times (5, 10, 15 and 20 min), solid to liquid ratio (1:20, 1:25, 1:30 and 1:35), and at constant stirring speeds (400 rpm). The optimum parameters resulted were 50 oC temperature, 5 min time and 1:20 S:L, and the leaching efficiencies of copper 59.7% was achieved with these optimum conditions. Copper precipitation, from nitric acid solution, were conducted using pure zinc powder at room temperature without stirring for 24 hour. Recovery efficiency of copper 99.93% was achieved